The Afrofuturism, postmodernism and postcolonialism: Theoretical decenterings and the epistemological critique from afrodiasporic arts (TEL Tempo, Espaço e Linguagem, 2023)
This article discusses the relationships between postmodernism and postcolonialism as theoretical approaches, and Afrofuturism as an aesthetic-political movement, highlighting the continuities and ruptures between both theoretical approaches, and between them and Afrofuturism. Our purpose is to discuss the theoretical decentering caused by the epistemological critique contained in Afrodiasporic arts and Afrofuturism. From the studies of the African diaspora, modernity and colonialism are positioned as great narratives in relation to the resistance projects generated by the Afrofuturist movement, indicating the re-elaboration of experiences through the arts as a way of renewing theoretical references.